MODERN PREBIOTICS IN CORRECTION OF INTESTINAL MICROBIOCENOSIS IN CHILDREN - I.N. Zakharova; L.N. Mazankova; Yu.A. Dmitrieva ("Paediatrician" Publishers LLC, 2009)
This article presents a data of role of normal micro flora of gastrointestinal tract in forming of alimentary functions and immune system of newborn. Processes of formation of intestinal micro biocenose, and pre and postnatal factors of development of dysbacteriosis in children of early age were analyzed. Authors give modern classification of probiotics. Results of trials show effectiveness and safety of combination of probiotiс cultures Bifidobacterium lactis BB-12 and Streptococcus thermophilus, forming new complex «Bifiform Baby» for children of early age. Key words: children of early age, normal micro flora, gastrointestinal tract, probiotics. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):109-113)